Future challenges of demographic changes - Kopač, Anja (Teorija in praksa, 2017)
This paper focuses on the need to reform the Slovenian pension system in order to adapt its functioning to the country's future demographic challenges. The theoretical part details the different types of welfare state along with the fundamental principles historically incorporated in the social security systems. A special part considers the demographic trends and their implications for the sustainability of Slovenia's pension system. The theoretical part is then applied to review whether the solutions proposed in the White Book on Pensions in fact follow the fundamentals of the welfare state and those principles that traditionally have roots in Slovenian society.
Keywords: Demografija; demografski razvoj; Demography; Država blaginje; Javne finance; Pensions; Pokojnine; Public finance; Slovenia; Slovenija; Welfare state